Subjective well-being among psychotherapists during the coronavirus disease pandemic: A cross-cultural survey from 12 european countries. (October 2022) - Van Hoy, Angelika; Rzeszutek, Marcin; Pięta, Małgorzata; Mestre, Jose M.; Rodríguez-Mora, Álvaro; Midgley, Nick; Omylinska-Thurston, Joanna; Dopierala, Anna; Falkenström, Fredrik; Ferlin, Jennie; Gergov, Vera; Lazić, Milica; et al.
Abstract: Objective: The aim of this study is to examine the amount of the total variance of the subjective well-being (SWB) of psychotherapists from 12 European countries explained by between-country vs. between-person differences regarding its cognitive (life satisfaction) and affective components (positive affect [PA] and negative affect [NA]). Second, we explored a link between the SWB and their personal (self-efficacy) and social resources (social support) after controlling for sociodemographics, work characteristics, and COVID-19-related distress. Methods: In total, 2915 psychotherapists from 12 countries (Austria, Bulgaria, Cyprus, Finland, Great Britain, Serbia, Spain, Norway, Poland, Romania, Sweden, and Switzerland) participated in this study. The participants completed the Satisfaction with Life Scale (SWLS), the International Positive and Negative Affect Schedule Short Form (I-PANAS-SF ), the General Self-Efficacy Scale, and the Multidimensional Scale of Perceived Social Support. Results: Cognitive well-being (CWB; satisfaction with life) was a more country-dependent component of SWB than affective well-being (AWB). Consequently, at the individual level, significant correlates were found only for AWB but not for CWB. Higher AWB was linked to being female, older age, higher weekly workload, and lower COVID-19-related distress. Self-efficacy and social support explained AWB only, including their main effects and the moderating effect of self-efficacy. Conclusions: The results highlight more individual characteristics of AWB compared to CWB, with a more critical role of low self-efficacy for the link between social support and PA rather than NA . This finding suggests the need for greater self-care among psychotherapists regarding their AWB and the more complex conditions underlying their CWB.